2004
DOI: 10.1074/jbc.m401705200
|View full text |Cite
|
Sign up to set email alerts
|

N-cadherin Activation Substitutes for the Cell Contact Control in Cell Cycle Arrest and Myogenic Differentiation

Abstract: N-cadherin is expressed throughout skeletal myogenesis and has been proposed to be involved in the differentiation program of myogenic precursors. Here, we further characterize the N-cadherin involvement and its mechanism of action at the onset of differentiation, through controlled N-cadherin activation by plating isolated C2 myoblasts on surfaces coated with a chimeric Ncad-Fc homophilic ligand (N-cadherin ectodomain fused to the immunoglobulin G Fc fragment). We show that N-cadherin activation substitutes f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
51
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 57 publications
4
51
1
Order By: Relevance
“…4). We also observed a significantly decreased expression of p27, a well known cdk inhibitor, which in synergy with MyoD, induces a withdrawal from the cell cycle and initiates differentiation (38,39).…”
Section: Expression and Activity Of Myogenic Transcription Factors Armentioning
confidence: 73%
See 1 more Smart Citation
“…4). We also observed a significantly decreased expression of p27, a well known cdk inhibitor, which in synergy with MyoD, induces a withdrawal from the cell cycle and initiates differentiation (38,39).…”
Section: Expression and Activity Of Myogenic Transcription Factors Armentioning
confidence: 73%
“…In regenerating muscles, we observed that MyoD and p27 expression was lower in Trpc1 Ϫ/Ϫ than in Trpc1 ϩ/ϩ regenerating muscles. These two proteins seem to induce cell cycle arrest in response to cell-cell contact and to promote myoblast differentiation (38,39). We therefore pro- pose that the decreased expression of MyoD and p27 might be a consequence of the delayed alignment and cell-cell contacts of Trpc1 Ϫ/Ϫ myoblasts.…”
Section: Discussionmentioning
confidence: 99%
“…The Cdo ectodomain does not interact with itself in trans and has no obvious adhesive properties, but it binds several proteins as a putative coreceptor (9,(11)(12)(13)(14). In myoblasts, Cdo forms cis complexes with the cell-cell adhesion molecule N-cadherin (Ncad) (11), which is itself promyogenic (15)(16)(17)(18)(19)(20). Cell-cell contact stimulates myoblast differentiation, and although Ncad is not essential for myogenesis (likely due to redundancy with other cadherins) (21), direct Ncad ligation can substitute for cell-cell contact to enhance muscle-specific gene expression and myoblast differentiation (17,19).…”
mentioning
confidence: 99%
“…Cell-cell contact stimulates myoblast differentiation, and although Ncad is not essential for myogenesis (likely due to redundancy with other cadherins) (21), direct Ncad ligation can substitute for cell-cell contact to enhance muscle-specific gene expression and myoblast differentiation (17,19). The ubiquitous cadherin-associated protein p120-catenin is important for Ncad's effects in myoblasts but the signaling mechanisms that drive a muscle-specific response are unknown (17,22). Cdo also binds directly to the secreted morphogen, Sonic hedgehog (Shh), perhaps as a coreceptor for Patched1, to promote Shh pathway signaling (13,14).…”
mentioning
confidence: 99%
See 1 more Smart Citation